Herbert Thorndike and the Restoration of the Church of England - Douglas, Brian, (Anglican-Episcopal Theology and History ;, 2025)
The Caroline theologian Herbert Thorndike (1598-1672) was significant before and after the seventeenth-century Restoration of the Church of England. Thorndike's theological methodology engaged with ecclesiology, the government and ministry of the Church of England, the Eucharist and the Book of Common Prayer . This book features Thorndike's significant reflection on eucharistic theology, based on ancient realist models but recast for the present. The book argues that Thorndike's theological methodology was useful in its own time but also has currency for Anglican and ecumenical theology discourse, particularly in relation to ecclesiology, eucharistic theology and liturgical theology and practice.